A Case Study in Adult Discipleship: Stories of Apprenticeship to Jesus at an Urban Anglican (Episcopal) Church - Siew, Yau Man (Christian education journal, 2021)
Anglican (Episcopal) churches around the world face a serious problem in discipleship and has called for a season of “intentional discipleship and disciple-making.” The Anglican Church of Canada renewed its emphasis on discipleship, providing some helpful resources, but there are no studies of how discipleship may be experienced at a congregational level. This study focuses on an Anglican church, identified as a leader in discipleship ministry. Through in-depth interviews and observations of formative events, I sought to discover how this congregation understood discipleship, engaged its Anglican tradition, lived and nurtured its reality in their context.